Path of awareness: the relationship between mindfulness and place - Chen, Anran (2023)
Mindfulness meditation has been increasingly used as a tool to address both physical and mental health issues in contemporary society and has gained growing interest and application in various fields. Meanwhile, designers have attempted to use architectural design to help improve people's well-being. However, the relationship between dedicated mindfulness practice and the physical environment in which it is practised awaits further exploration. This study aimed to investigate how spatial design can facilitate formal mindfulness practice. To do so, this research examined a wide range of literature, including related mindfulness theories originating in the Buddhist tradition, architectural and landscape design, and environmental psychology. It established an initial research framework for empirical study and application.